Business cycle synchronization of the Visegrad Four and the European Union - Lubos Hanus; Lukas Vacha (Charles University in Prague, Institute of Economic Studies (IES), 2015)
In this paper, we map the process of synchronization of the Visegrad Four within the framework of the European Union using wavelet techniques. We show that the relationship of among countries is dynamic and that it varies over time and across frequencies. We study the synchronization applying the wavelet cohesion measure with time-varying weights. This novel approach allows us to study the dynamic relationship among countries from a different perspective than the usual timedomain models. Analyzing monthly data from 1990 to 2014, the results for the Visegrad region show an increasing co-movement with the European Union after the countries began preparing for accession to the European Union. Participation in a currency union possibly increases the co-movement. Furthermore, we find a high degree of synchronization in long-term horizons by analyzing the Visegrad Four and Southern European countries' synchronization with the core countries of the European Union.
Keywords: E32; C40; F15; 330; business cycle synchronization; time-frequency; wavelets; co-movement; Visegrad Four; European Union